2021
DOI: 10.1007/s00784-021-04049-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a one-item version of the Orofacial Esthetic Scale

Abstract: Objectives Orofacial appearance is increasingly recognized as an important dental patient-reported outcome making instrument development and refinement efforts to measure the outcome better necessary. The aim of this study was to derive a one-item version of the Orofacial Esthetic Scale (OES). Materials and methods OES data were collected from a consecutive sample of a total of 2113 adult English- or Spanish-speaking dental patients from HealthPartners den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The OEQ was utilized in this study as the study tool to assess how the participating patients felt about their orofacial look. The successful use of OEQ in previous studies with similar objectives has been reported in the literature [22][23][24][25][26][27][28][29][30]. To assess the overall satisfaction of the participating patients with their esthetic appearance prior to LRS, after one month, after six months, and after one year following the surgery, the patients' satisfaction levels regarding their orofacial condition were targeted in all the questions asked.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The OEQ was utilized in this study as the study tool to assess how the participating patients felt about their orofacial look. The successful use of OEQ in previous studies with similar objectives has been reported in the literature [22][23][24][25][26][27][28][29][30]. To assess the overall satisfaction of the participating patients with their esthetic appearance prior to LRS, after one month, after six months, and after one year following the surgery, the patients' satisfaction levels regarding their orofacial condition were targeted in all the questions asked.…”
Section: Discussionmentioning
confidence: 96%
“…When time and resources are limited, the OEQ is a quick and easy-to-use questionnaire that can be used to assess the face and oral esthetics of dental patients [ 29 ]. The OEQ is a practical and time-saving tool for epidemiological studies, national health surveys, and ordinary dentistry practice where a multi-item OEQ questionnaire is not viable due to a larger patient sample size [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the OES was originally designed to assess prosthodontic patients, it has been shown that it may be applicable among tooth‐wear patients (S325). Recently, a 1‐item version of the OES was developed, rendering it a more effective tool 13 . Dental healthcare providers may elect to use the Prosthetic Aesthetic Index, PEI 14,15 to undertake a professional evaluation of aesthetics.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a 1-item version of the OES was developed, rendering it a more effective tool. 13 Dental healthcare providers may elect to use the Prosthetic Aesthetic Index, PEI 14,15 to undertake a professional evaluation of aesthetics. Another instrument that can be applied is 3D-stereo photograph imaging technology, which may be used when undertaking comprehensive treatment planning for patients with severe tooth wear (S297, S298).…”
Section: Impaired Aestheticsmentioning
confidence: 99%